A microfluidic application for mass production of drug-loaded polymeric microspheres for a long-acting injectable with IVL-DrugFluidic®, a novel microfluidic microsphere manufacturing platform technology - Chan Hee Chon; Ju Hee Kim; Hyunseung On; Jiwoong Choi; Sanghun Lee; Euidon Han (Elsevier, 2023)
Long acting injectables (LAIs) using polymeric microspheres has been developed to increase patient compliance and reduce side effects. Among many methods for manufacturing polymeric microspheres, microfluidics technology is known to have excellent characteristics in that the produced polymeric microspheres have perfect spherical shape without surface defect and uniform size, and thus have outstanding efficacy without initial burst. However, the mass production of polymeric microspheres was not realized by the inherent limitation that microfluidics is suitable for small quantity manufacturing. Overcoming such limitations, we could show mass production of finasteride-loaded polymeric microspheres (PLGA 7525) for LAIs using our microfluidic manufacturing platform technology, IVL-DrugFluidic®. The microfluidic channels used in manufacturing were optimized through computational fluid dynamics (CFD) simulation to minimize the flow variation between microchannels and eliminated disturbance outside of microchannels by resistance channels. In addition, the solvent removal was improved by applying the baffle and foam breaker system. Therefore, microspheres were mass-produced in the GMP manufacturing environment in perfect spherical shape, smooth surface, and even size distribution. The encapsulation efficiency was almost 100% and the residual solvent was under the Standard of regulation. In the clinical trial using microspheres mass-produced by IVL-DrugFluidic®, we confirmed that the drug release was stably maintained for a month, the target period without initial burst. It was also confirmed that the drug release by dose of microspheres was uniformly proportional. In conclusion, the microsphere manufacturing platform technology, IVL-DrugFluidic® has been proven to be an appropriate system for mass production of polymeric microspheres optimized for LAIs through physicochemical characteristics and clinical trial.